1987
DOI: 10.1080/00223980.1987.9712651
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Obsessive-Compulsive Personality to Obsessive-Compulsive Disorder: A Review of the Literature

Abstract: The nature of the relationship between obsessive-compulsive personality and obsessive-compulsive disorder has been the subject of considerable debate. The present article dealt with clinical opinion and reviewed empirical data bearing on this issue. It was concluded that, although the two clinical entities bear a surface similarity in terms of shared behavioral features and defenses, obsessive-compulsive personality is neither a necessary nor sufficient factor in the development of obsessive-compulsive disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 42 publications
1
17
0
2
Order By: Relevance
“…Unfortunately, the nature of this relation has been murky due to a blurring of the distinction Freud (1917) made between the constructs now labeled OCD and Obsessive-Compulsive Personality Disorder (OCPD)-only the latter of which includes perfectionism as a formal diagnostic criterion (American Psychiatric Association, 2000). Generally, however, research has established the independence of OCD and OCPD (Pollak, 1987), allowing for specific clarification of OCD-personality associations. Wu, Clark, and Watson (2006) found that whereas a unique OCD-OCPD relation was not supported, certain personality traits (e.g., very low impulsivity) distinguished individuals with OCD versus a primarily depressed group.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, the nature of this relation has been murky due to a blurring of the distinction Freud (1917) made between the constructs now labeled OCD and Obsessive-Compulsive Personality Disorder (OCPD)-only the latter of which includes perfectionism as a formal diagnostic criterion (American Psychiatric Association, 2000). Generally, however, research has established the independence of OCD and OCPD (Pollak, 1987), allowing for specific clarification of OCD-personality associations. Wu, Clark, and Watson (2006) found that whereas a unique OCD-OCPD relation was not supported, certain personality traits (e.g., very low impulsivity) distinguished individuals with OCD versus a primarily depressed group.…”
Section: Introductionmentioning
confidence: 98%
“…48 Our study is the first, to our knowledge, to investigate OCPD among the relatives of women with EDs. Rates were elevated among relatives of AN probands, irrespective of the presence of OCPD among the probands themselves.…”
Section: Obsessive-compulsive Personality Disordermentioning
confidence: 99%
“…The checking, washing, and other compulsive rituals of OCD have been viewed as pathological intrusions into an otherwise intact personality. OCPD is generally less impairing than OCD, and may be one of the less impairing of the personality disorders, since these traits may be adaptive, especially in certain occupational realms (Pollak, 1987). Interestingly, the two disorders share behavioural features, including emotional constriction, self-doubt, low risk-taking, indecisiveness, and perfectionism.…”
mentioning
confidence: 98%
“…Surveys of the incidence of comorbidity reveal that OCPD is not a necessary or sufficient factor in development of OCD. Still, individuals with OCPD traits are likely to be more prone to OCD than individuals without these traits (Pollak, 1987). Samuels et al (2000) reported that OCD patients and their first-degree relatives demonstrated an increased incidence of OCPD relative to control subjects and their first-degree relations.…”
mentioning
confidence: 98%
See 1 more Smart Citation